EVALUASI PROGRAM KESEHATAN DAN HYGIENE KARYAWAN DALAM PENERAPAN GMP PADA UMKM SAMBAL TUNA UMMI ZEE CILACAP - SHAFIRA ZAHROH; SUNU PANGESTUTI; EGA KARISA GIOVANNI; SYACHRUL LUHUR PRAMONO; SARI WIDYA UTAMI (Jurnal Agroindustri Pangan, 2025)
The food processing industry in Indonesia continues to grow, driven by increasing consumer awareness of food safety. Most food businesses have implemented good sanitation and hygiene practices, such as providing handwashing facilities, maintaining clean toilets, and encouraging employees to wash their hands before and after production. However, issues remain, including the improper use of work attire and jewelry during production, which pose contamination risks. This underscores the need for stricter supervision and routine training to enhance compliance with GMP standards. The evaluation aims to provide a realistic overview of GMP implementation in MSMEs and serve as a basis for improvements to enhance product quality and safety.